Role of the C2B domain of synaptotagmin in vesicular release and recycling as determined by specific antibody injection into the squid giant synapse preterminal. - Fukuda, M (1995)
Synaptotagmin (Syt) is an inositol high-polyphosphate series [IHPS inositol 1,3,4,5-tetrakisphosphate (IP4), inositol 1,3,4,5,6-pentakisphosphate, and inositol 1,2,3,4,5,6-hexakisphosphate] binding synaptic vesicle protein. A polyclonal antibody against the C2B domain (anti-Syt-C2B), an IHPS binding site, was produced. The specificity of this antibody to the C2B domain was determined by comparing its ability to inhibit IP4 binding to the C2B domain with that to inhibit the Ca2+/phospholipid binding to the C2A domain. Injection of the anti-Syt-C2B IgG into the squid giant presynapse did not block synaptic release. Coinjection of IP4 and anti-Syt-C2B IgG failed to block transmitter release, while IP4 itself was a powerful synpatic release blocker. Repetitive stimulation to presynaptic fiber injected with anti-Syt-C2B IgG demonstrated a rapid decline of the postsynaptic response amplitude probably due to its block of synaptic vesicle recycling. Electron microscopy of the anti-Syt-C2B-injected presynapse showed a 90% reduction of the numbers of synaptic vesicles. These results, taken together, indicate that the Syt molecule is central, in synaptic vesicle fusion by Ca2+ and its regulation by IHPS, as well as in the recycling of synaptic vesicles.